Social games and game-based revenue models - Balnaves, Mark; Madden, Gary (2016)
Casual, social games are estimated to engage more than 200 million world-wide with revenues of US$6 billion on mobile, iPond, social networks, PC, Mac, Xbox LIVE Arcade platforms (CGA 2013). The name of the game is freemium for this economy. Freemium provides players with free access to games. Those players who want to upgrade the look and feel of the game or other additional amenities pay for it. Tetris, created in a Soviet lab, was arguably the first casual game, tied to the Japanese Game Boy in its creation. Tetris was also the first casual game to show the possibilities of monetization of this phenomenon. In this chapter the authors look at the games-based revenue models and how they are evolving, providing a background to the development of the industry itself.